Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13075-018-1762-1
|View full text |Cite|
|
Sign up to set email alerts
|

Standardisation of synovial biopsy analyses in rheumatic diseases: a consensus of the EULAR Synovitis and OMERACT Synovial Tissue Biopsy Groups

Abstract: BackgroundThe aim of this global collaboration was to develop a consensual set of items for the analysis of synovial biopsies in clinical practice and translational research through the EULAR Synovitis Study Group (ESSG) and OMERACT Synovial Tissue Biopsy Group.MethodsParticipants were consulted through a modified Delphi method. Three sequential rounds occurred over 12 months. Members were sent a written questionnaire containing items divided into two parts. Items were identified and formulated based on a scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 24 publications
(25 reference statements)
0
38
0
1
Order By: Relevance
“…In conclusion, in the present report, we revealed that the reduction of α2 For active naïve and remission RA patients 59 , biopsies were collected using a standard operating procedure with sampling of at least 6-8 different tissue pieces as required by the international recommendations for synovial tissue analysis 60,61 .…”
Section: Discussionmentioning
confidence: 76%
“…In conclusion, in the present report, we revealed that the reduction of α2 For active naïve and remission RA patients 59 , biopsies were collected using a standard operating procedure with sampling of at least 6-8 different tissue pieces as required by the international recommendations for synovial tissue analysis 60,61 .…”
Section: Discussionmentioning
confidence: 76%
“…Detailed analysis of synovial tissue biopsies (STB) is likely to reveal urgently needed, robust biomarkers that will guide clinical decisions, and stratify patients according to their disease subgroup and predicted response to treatment. With this in mind, Najm and colleagues have undertaken a consensus exercise to identify factors that are important for the reliability and reproducibility of STB analysis across centres [1].…”
Section: Editorialmentioning
confidence: 99%
“…However, the fourth—standardisation in the handling, evaluation and interpretation of STB—requires considerable effort from the international rheumatology community to reach consensus. Najm et al have now established a list of consensus points for standardised STB handling and analytical procedures in two situations—clinical practice and translational research [1]—and upon which a standardisation framework can be built. This task force used a modified Delphi analysis (structured anonymised questionnaire answered independently by a panel of experts) considering factors linked to biopsy sampling, processing, histological criteria, immunohistochemistry analysis, STB interpretation and pathologists report for both situation, and also RNA analysis for translational research [1].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [1], the authors reported an error in the spelling of the ninth author’s name.…”
mentioning
confidence: 99%